1994
DOI: 10.1016/s0006-3495(94)80591-0
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-beta aggregation: selective inhibition of aggregation in mixtures of amyloid with different chain lengths

Abstract: One of the clinical manifestations of Alzheimer's disease is the deposition of the 39-43 residue amyloid-beta (A beta) peptide in aggregated fibrils in senile plaques. Characterization of the aggregation behavior of A beta is one of the critical issues in understanding the role of A beta in the disease process. Using solution hydrodynamics, A beta was observed to form three types of species in phosphate-buffered saline: insoluble aggregates with sedimentation coefficients of approximately 50,000 S and molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
239
2
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(269 citation statements)
references
References 55 publications
24
239
2
1
Order By: Relevance
“…Our observations show that variations in the Ab sequence can have consequences for the propensity of the Ab peptide to aggregate and oligomerize. C-terminal variation was previously shown to affect aggregation propensity, and it has been generally reported that Ab aggregates at a higher rate than Ab 1-40 [20,21]. Even though approximately 90% of the Ab peptide pool is composed of these two peptides, it was recently recognized that also Ab 1-37 , Ab , and Ab are present in the brain and may modulate disease progress [22].…”
Section: Discussionmentioning
confidence: 99%
“…Our observations show that variations in the Ab sequence can have consequences for the propensity of the Ab peptide to aggregate and oligomerize. C-terminal variation was previously shown to affect aggregation propensity, and it has been generally reported that Ab aggregates at a higher rate than Ab 1-40 [20,21]. Even though approximately 90% of the Ab peptide pool is composed of these two peptides, it was recently recognized that also Ab 1-37 , Ab , and Ab are present in the brain and may modulate disease progress [22].…”
Section: Discussionmentioning
confidence: 99%
“…The Aβ peptides vary in size from 39 to 42 amino acids, and Aβ 1−42 aggregates more readily than the other molecules (35). A GxxxG sequence motif within the transmembrane domain has been implicated in homodimerization (36) and in cholesterol-binding (37) (Figure 1B).…”
Section: Aβ Transmembrane Domain and Intracellular Domainmentioning
confidence: 99%
“…Quasielastic light-scattering measurements revealed that SEC-purified Aβ protofibrils contained aggregates with hydrodynamic radii (R H ) of 10-50 nm, which correspond to lengths of ~30-500 nm for noninteracting rods 13 . The heterogeneity of protofibrils was further elucidated by scanning transmission electron microscopy (TEM) 18 and sedimentation velocity measurements 57 . These studies revealed that protofibrils are a population of aggregates with molecular weight distribution ranging from 80 kDa to ~1 mDa (ref.…”
Section: High Molecular Weightmentioning
confidence: 99%
“…Although these preparations are free of protofibrillar or fibrillar aggregates, the presence of unstable LMW oligomers (dimers, trimers, and so on) that are in rapid equilibrium with the major monomeric species has been suggested and cannot be ruled out. To prepare protofibrillar Aβ fractions, the peptide is initially dissolved in DMSO 57 and then aggregation is promoted under high-salt conditions. This leads to the generation of a solution enriched with Aβ protofibrils and monomers.…”
Section: Centrifugedmentioning
confidence: 99%